Peran Kecerdasan Intelektual dan Emosional dalam Meningkatkan Kompetensi dan Kinerja Karyawan - Diansyah, Rahmat; Lazi, Usman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study analyzes the impact of intellectual intelligence (IQ) and emotional intelligence (EQ) on employee competence and performance. The main objective of this research is to examine the relationship between these two types of intelligence and the work outcomes achieved by employees. Data was collected through a questionnaire distributed to 200 respondents working at XYZ company, who have over one year of experience. The descriptive analysis results show that intellectual intelligence positively affects employee performance, with most respondents demonstrating the ability to handle tasks that require logical thinking. Meanwhile, emotional intelligence plays a role in maintaining harmonious relationships and managing stress, although its direct impact on employee performance was not found to be significant. Based on multiple regression analysis, intellectual intelligence and competence have a significant impact on performance, while emotional intelligence does not show a direct, significant effect. This study suggests that companies should focus on enhancing intellectual intelligence through analytical skill training and strengthen emotional intelligence to create a better work environment that supports higher performance. The findings provide guidance for developing more effective human resource policies to improve organizational performance.